2021
DOI: 10.1021/jacs.1c03270
|View full text |Cite
|
Sign up to set email alerts
|

Nonrefoldability is Pervasive Across the E. coli Proteome

Abstract: Decades of research on protein folding have primarily focused on a subset of small proteins that can reversibly refold from a denatured state. However, these studies have generally not been representative of the complexity of natural proteomes, which consist of many proteins with complex architectures and domain organizations. Here, we introduce an experimental approach to probe protein refolding kinetics for whole proteomes using mass spectrometry-based proteomics. Our study covers the majority of the soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 56 publications
8
77
0
Order By: Relevance
“…In preliminary experiments, we tested whether cyto-serum would be suitable for global refolding experiments by measuring the levels of aggregation that accrue after 2 h. Pelleting assays detected low but non-zero levels of aggregation (6 ± 2% of protein), in contrast with the buffer conditions we had previously devised (20 mM Tris pH 8.2, 100 mM NaCl, 2 mM MgCl2, 1 mM DTT) that result in very low levels of precipitation (3 ± 1%, Figure 1-figure supplement 2D). This 3% increase in aggregation is close to what we previously observed for refolding in a defined buffer at neutral pH (To et al, 2021;Wang et al, 2017), thereby confirming that alkaline pH helps suppress aggregation, and that the cytosolic components do not increase aggregation levels beyond an expected effect from pH. To further investigate aggregation (including smaller soluble non-precipitating aggregation), we performed sedimentation velocity analytical ultracentrifugation (AUC) and mass photometry (MP) on these refolding reactions (Figure 1-figure supplement 3).…”
Section: A Methods To Interrogate Refolding the E Coli Proteome In Cy...supporting
confidence: 90%
See 3 more Smart Citations
“…In preliminary experiments, we tested whether cyto-serum would be suitable for global refolding experiments by measuring the levels of aggregation that accrue after 2 h. Pelleting assays detected low but non-zero levels of aggregation (6 ± 2% of protein), in contrast with the buffer conditions we had previously devised (20 mM Tris pH 8.2, 100 mM NaCl, 2 mM MgCl2, 1 mM DTT) that result in very low levels of precipitation (3 ± 1%, Figure 1-figure supplement 2D). This 3% increase in aggregation is close to what we previously observed for refolding in a defined buffer at neutral pH (To et al, 2021;Wang et al, 2017), thereby confirming that alkaline pH helps suppress aggregation, and that the cytosolic components do not increase aggregation levels beyond an expected effect from pH. To further investigate aggregation (including smaller soluble non-precipitating aggregation), we performed sedimentation velocity analytical ultracentrifugation (AUC) and mass photometry (MP) on these refolding reactions (Figure 1-figure supplement 3).…”
Section: A Methods To Interrogate Refolding the E Coli Proteome In Cy...supporting
confidence: 90%
“…(2) our previous study (To et al, 2021) confirmed that refolded/native protein abundance ratios were equal to unity at a frequency higher than the false discovery rate.…”
Section: Limited Proteolysis Mass Spectrometry Sample Preparationmentioning
confidence: 62%
See 2 more Smart Citations
“…To our knowledge, no representative samples of proteins have been studied under this angle until very recently. However, in a recent proteome-wide study, protease-resistance assay was used in combination with quantitative mass-spectrometry to show that about 50% of the proteins in E. coli cell lysates could not refold into their native states following chemical denaturation, even when the conditions were optimized for refolding [ 71 ]. These findings indicate that non-refoldability in vitro is a general characteristic of at least this bacterial proteome, especially, taking into consideration that the completeness of unfolding was not monitored in these experiments.…”
Section: Review Of Protein Foldingmentioning
confidence: 99%